Temperature control system for infant incubator using DS18B20 sensor - Laila Katriani; Arif Setiawan; Denny Darmawan (Jurnal Sains Dasar, 2014)
A temperature control system for infant incubator using DS18B20 had been built. The dimension of the incubator was 45 x 35 x 35 cm3 and it used 200 W incandescent lamp as an heater element. The system was automated using ATMEGA328P and Triac as an actuator. It succeeded in keeping the incubator temperature at (36.5 ± 0.1) °C. It took around 10 minutes to reach the working temperature of 36.5 °C from room temperature of 26 °C.   Key words: temperature control system, infant incubator, DS18B20